A suicidal strain of Listeria monocytogenes is effective as a DNA vaccine delivery system for oral administration. Issue 38 (12th September 2017) - Sinha, Shubhra; Kuo, Cheng-Yi; Ho, Joan K.; White, Paul J.; Jazayeri, Jalal A.; Pouton, Colin W.
Abstract: In this study we determined the in vivo activity of model ovalbumin vaccines delivered by direct intramuscular delivery of plasmid DNA or oral delivery using a recombinant suicidal Listeria monocytogenes strain (rsΔ2). In a previous report we described how rsΔ2 is capable of delivering luciferase, as protein or DNA, in vitro, into non-dividing intestinal epithelial cells (Kuo et al., 2009). This is achieved by engineering a dual expression shuttle vector, pDuLX-Luc, that replicates in E. coli and rsΔ2 and drives gene expression from the Listeria promoter (P hly ) as well as the eukaryotic cytomegalovirus promoter (CMV), thereby delivering both protein and plasmid DNA to the cell cytoplasm. For the current in vivo study rsΔ2 containing pDuLX-OVA was used to deliver both ovalbumin protein and the mammalian expression plasmid by the oral route. Controls were used to investigate the activity of this system versus positive and negative controls, as well as quantifying activity against direct intramuscular injection of expression plasmids. Oral administration of rsΔ 2(pDuLX-OVA) produced significant titres of antibody and was effective at inducing targeted T-cell lysis (approximately 30% lysis relative to an experimental positive control, intravenous OVA-coated splenocytes + lipopolysaccharide). Intramuscular injection of plasmids pDuLX-OVA or p3L-OVA (which lacks the prokaryotic promoter) also produced significant CTL-mediated cell lysis. The delivery of the negative control rsΔ 2 (pDuLX-Luc) confirmed that the observed activity was induced specifically by the ovalbumin vaccination. The data suggest that the oral activity of rsΔ2(pDuLX-OVA) is explained by delivery of OVA protein, expressed in rsΔ2 from the prokaryotic promoter present in pDuLX-OVA, but transfection of mammalian cells in vivo may also play a role. Antibody titres were also produced by oral delivery (in rsΔ2) of the p3L-OVA plasmid in which does not include a prokaryotic promoter.